Trypanosoma brucei RRP44 is involved in an early stage of large ribosomal subunit RNA maturation - Cesaro, Giovanna (2019)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES Financing code 001 and CAPES-COFECUB grant 862-15), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq, NITZ 312195/2015-0 and GC fellow-ship) and Fundação Oswaldo Cruz.